2007
DOI: 10.2134/agronj2006.0287
|View full text |Cite
|
Sign up to set email alerts
|

Choice of Summer Fallow Replacement Crops Impacts Subsequent Winter Wheat

Abstract: Winter wheat (Triticum aestivum L.) is the foundation of dryland cropping systems in the Central Great Plains. The objective of this study was to quantify the effects of four short‐season spring‐planted crops used to replace summer fallow on the subsequent winter wheat crop. Wheat was seeded into four crop stubbles [spring triticale (×Triticosecale Wittmack), dry pea (Pisum sativum L.), foxtail millet (Setaria italica L. Beauv.), and proso millet (Panicum miliaceum L.)] at sites near Akron, CO, and Sidney, NE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 26 publications
3
33
0
Order By: Relevance
“…Soil water content at planting has a strong influence on crop yield Nielsen and Vigil, 2005;Felter et al, 2006, Lyon et al, 2007Nielsen et al, 2008). Therefore, data from the first five years of the study (1991)(1992)(1993)(1994)(1995) are not considered in the analysis presented in the paper (1996-2011) as we considered those years to be the time period in which the rotations were being established and from which time forward the true effects of the rotational sequences, primarily due to differences in soil water content, could be evaluated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil water content at planting has a strong influence on crop yield Nielsen and Vigil, 2005;Felter et al, 2006, Lyon et al, 2007Nielsen et al, 2008). Therefore, data from the first five years of the study (1991)(1992)(1993)(1994)(1995) are not considered in the analysis presented in the paper (1996-2011) as we considered those years to be the time period in which the rotations were being established and from which time forward the true effects of the rotational sequences, primarily due to differences in soil water content, could be evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…They did not report consistent effects of previous crop type on WUE of spring wheat, but WUE was generally lower when wheat was preceded by a crop than when wheat was preceded by a fallow period. Lyon et al (2007) reported results from a 2-year study conducted at two central Great Plains locations (Nebraska Panhandle, northeastern Colorado) in which the effects of preceding crop (triticale [X Triticosecale Wittmack], pea, foxtail millet [Setaria italica L. Beauv.…”
Section: Introductionmentioning
confidence: 99%
“…Our results cannot be directly compared with other studies as there is limited information on CC effects on soil properties in the central Great Plains under no-till conditions. Most previous studies in this region focused on water use and grain yields in CCs used as green manure under conventional till (Schlegel and Havlin, 1997;Nielsen and Vigil, 2005;Felter et al, 2006;Lyon et al, 2007).…”
Section: Cover Cropmentioning
confidence: 99%
“…Th e simulations by Zhang (2003) were performed in a region where the 28-yr growing season precipitation average was ~485 mm, suggesting that PAW s may be a stronger limiting factor to wheat grain yields in the western portion of the Great Plains, region characterized by lower growing season precipitation. Indeed, Lyon et al (2007), Norwood (2000), and Stone and Schlegel (2006) found reduced wheat yields associated with reduced PAW s in Colorado and western Kansas, highlighting the positive linear relationship between PAW s and rainfed wheat yields in wheat-fallow systems in the Great Plains.…”
mentioning
confidence: 95%